Axial load behavior of structural bamboo filled with concrete and cement mortar. (1st September 2017) - Li, Wen-Tao; Long, Yue-Ling; Huang, Jun; Lin, Yan
Highlights: The axial load behavior of material-filled structural bamboo was investigated. The effects of infilled materials, horizontal stiffener and node were investigated. The confining effects of bamboo were considered carefully in the study. Abstract: Bamboo has been widely used as a rapidly renewable structural material to build permanent and temporary structures in past decades. However, the compressive bearing capacity of bamboo is relatively low, which limits its applications only in the structures under light loads. This paper proposed an innovative scheme to improve the load bearing capacity of bamboo by filling concrete or cement mortar in bamboo cavity. An experimental study on the axial load behavior of material-filled structural bamboo was carried out, aiming at investigating the effects of the infilled materials, the horizontal stiffener and the bamboo node. A total of 19 specimens were tested under axial compression. It was found that the axial load bearing capacities and the initial stiffness of both concrete-filled bamboo columns and cement mortar filled bamboo columns are much higher than the conventional bamboo, which verified the feasibility of the proposed stiffening scheme. Concrete-filled bamboo columns show better ductility than cement mortar filled bamboo columns. Furthermore, the ductility of concrete-filled bamboo columns can be improved by increasing the steel reinforcement ratio. In addition, the beneficial effect of the node on the ultimate bearing capacity can be found in material-filled bamboo specimens, indicating that the integrity of the bamboo node is essential for the bearing capacities of material-filled bamboo columns. Similarly, the horizontal stiffener passing through bamboo internode has a beneficial effect on both the ultimate bearing capacities and the corresponding axial strains of material-filled bamboo columns and conventional bamboo. However, the stiffener passing through the node may result in a decease in the bearing capacity. Finally, a simple and efficient method was proposed for predicting the ultimate bearing capacity of material-filled bamboo columns. The confining effects of bamboo on the infilled materials are considered carefully in this method. The calculated results by the proposed method were compared with experimental results, exhibiting a good agreement.